Modern technologies of refractory glaucoma treatment. Review - A. Yu. Rascheskov; I. A. Loskoutov (Oftalʹmologiâ, 2014)
this article presents a review of available literature concerning basic directions of refractory glaucoma treatment. the surgical management of refractory glaucoma is presented by two main groups of surgical techniques: filtering surgery (including surgery with the use of antimetabolites and implants) and cyclodestructive procederes. types of glaucoma drainages are described, modern valve drainage system is presented.